Analysing online Twitter discussions of bedwetting via a condition‐specific hashtag (#Bedwetting). (19th May 2021) - Balasubramanian, Adithya; Dang, Melissa; Yu, Justin; Gerber, Jonathan A; Seth, Abhishek
Abstract : Aim: Bedwetting is a common paediatric condition. #Bedwetting has been established as the official hashtag to structure Twitter discussions about the condition. We analysed online Twitter discussions for #Bedwetting. Methods: Symplur, a Twitter analytics service was employed to aggregate Twitter activity, users and content including #Bedwetting, between October 2013 and November 2018. Activity was analysed via tweet volume and user adoption. Users were assorted using geographic location, occupation and affiliation data. Content in #Bedwetting Tweets was undertaken by retrieving information about retweets, links, frequently used words and hashtags. Results: A total of 101 412 tweets and 9957 users utilising #Bedwetting were identified. Most tweets were sent with links (93%). The average ± SD number of tweets using #Bedwetting per month increased from 96 ± 87 in 2013 to 2935 ± 1644 in 2015. Tweet volume decreased to 1960 ± 257 in 2016 and subsequently increased to 2901 ± 1110 in 2017. New users increased from 4 in 2013 to 9957 users in 2018. Users tweeted from 69 countries. Advocacy organisations comprised 35% of the top 100 influencers. Common words in #Bedwetting tweets were 'potty', 'best' and 'training'. Popular associated hashtags were #Pottytraining, #Solutions and #Moms. Hyperlinks in #Bedwetting tweets included advocacy, academic and commercial websites. Conclusions: Our analysis of #Bedwetting highlights that Twitter is frequently used to discuss the condition's diagnosis and management. Various stakeholders in health care are utilising the platform to build awareness about bedwetting. We identified that Twitter is being employed to drive web traffic to other internet websites.